The coherence in the human development and integral healt - Uresti-Marín, Rocío M. (Universidad Autónoma de Tamaulipas, 2013)
Reaching integral health is the main challenge in the development of human beings to maintain a high quality of life. Attaining integral health requires paying attention to all aspects of life: physical (body), mental, emotional (soul), and spiritual. Coherent human development in all these areas contributes to create a healthier society. As numerous studies have found,  those subjected to family changes, social and cultural ruptures characterized by emotional instability and social disorganization, are at greater risk of different types of emotional and mental illnesses that affect physical health. To achieve integrated health, an orderly and coherent development is required in the different stages of the life of an individual, catering different development areas. Family support and appropriate food for each area are also required. This article reviews scientific advances related to coherence in integral development and health care.